KEPERCAYAAN PUBLIK TERHADAP PENGAWASAN KEPABEANAN DI PERBATASAN INDONESIA-TIMOR LESTE - Wiratmoko, Doris; Djani, William; Susanti, Susanti (Jurnal Administrasi Negara, 2024)
This research intends to analyze the Public Trust's customs supervision of imports at the Indonesia-Timor Leste border in the KPPBC TMP B Atambua supervision area. Increasing customs supervision is very necessary for economic growth by increasing national income through various programs, one of which is exports and imports. The progress of exports and the reduction of imports are the benchmarks for a country's success. The problem is the slow rate of GRDP growth where in the last 5 (five) years Belu (Atambua) Regency has been ranked number 8 (eight) in the province of East Nusa Tenggara, which is a potential place for increasing economic progress in the border areas between Indonesia and Timor Leste. Apart from that, there are still many customs violations in the Indonesia - Timor Leste border area which have an impact on decreasing public confidence in customs supervision at KPPBC TMP B Atambua. The main theoretical basis used is supervision theory. This research uses a qualitative approach. The data sources in this research consist of primary and secondary data. Primary data was obtained from interviews, observation and documentation. Meanwhile, secondary data is also used in the data collection process, obtained from data including: Government Agency Performance Accountability Reports (LAKIN), Service User Satisfaction Surveys (SKPJ), and other documents. The research results show that accountability, synergy and collaboration, motivation, consistency, socialization of regulations, and public awareness influence Public Trust in government agencies or bureaucracy, especially KPPBC TMP B Atambua.